Baseball hitting accuracy and contributing factors - Higuchi, T.; Nagami, T.; Kanosue, K. (Sports Performance, 2015)
The purpose of this chapter is to discern the relationship between spatial accuracy, timing accuracy, and bat control and hitting accuracy for elite collegiate baseball batters. Nine college baseball batters performed three tasks. The first task was hitting a fastball thrown by a pitching machine (HPT). The second task was observing a pitching machine`s fastball and indicating the location (OPT). The third task was hitting a ball on a baseball tee (TBT). The subjects` performance in hitting accuracy was defined by their success rate in the HPT. The distribution of the point of ball-bat impact in the TBT represented the subjects` ability in the bat control. The fluctuations in the location in pitcher-to-catcher direction between the HPT and the TBT represented the subjects` temporal accuracy. The subjects` spatial accuracy was defined by their performance in the OPT. Although they were able to control their bat swings to hit a ball within the effective impact area most of the time in the Tee Ball Task, timing and spatial components of their performance indicated larger errors and lower precision. Our results suggest that the perceptual skills involved in baseball hitting are the main reason why batters fail to hit a ball accurately.